El momento de entrada en el mercado y la generación de ventajas competitivas sostenibles - P. M. García Villaverde; M. J. Ruiz Ortega (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
The literature on the pioneer strategy has been very extensive during the last two decades of last century. Opposite to the researches that have detected a direct effect of the pioneer entry on firm performance, some authors indicate the existence of a series of biases in the majority of the empirical studies that question the obtaining of conclusive results. The aim of this paper is to develop an explanatory model that, from a dynamic perspective, allows us to study in an integrated way the process of decision of the pioneer entry in the market and the influence of the moment of entry on the generation and sustainability of competitive advantages. With this aim we develop a review of the theoretical and empirical literature on the pioneering strategy and raise a series of theoretical propositions. These propositions form an explanatory model. Finally, we discuss the model and propose future lines of research.
Keywords: 330; moment of entry; pioneer strategy; theoretical propositions; empirical synthesis